Assembly research of aero-engine casing involving bolted connection based on rigid-compliant coupling assembly deviation modeling. (July 2020) - Kang, Hehe; Li, Zhi-Min
Assembly analysis is necessary for mechanical product to optimize design and improve the product quality since assembly deviation is the key factor affecting the assembly quality. In this paper, the rigid-compliant assembly of thin-walled aero-engine casing is studied to evaluate the assembly quality at the design stage. First, the Jacobian–Torsor model is proposed to construct multistage casing assembly owing to its effectiveness to express assembly deviation. The torsor expression is modified and expanded to present the rigid-compliant coupling tolerance. Then, the partial parallel chain is addressed via combination operation. By using extremum and statistical method, the tolerance zone and the distribution of the objective deviation are obtained. Furthermore, to study the effect of specified compliant deviation on statistical distribution, the bolt looseness and positional deformation are investigated to provide an effective means for geometric deviation and connecting joints of aero-engine casing components of precision assembly. The presented method can address compliant deformation tolerance and geometrical manufacturing tolerance together, and is reliable for casing assembly to predict assembly quality at the design stage. In addition, it also has a great significance to guide tolerance design and product optimization.